(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the impact of core-centered Pilates training on strength and stability parameters in elite Kabaddi players. The research aimed to evaluate the effects of an eight-week Pilates training program on core endurance, explosive power, and dynamic balance. A total of 40 male Kabaddi players from Adikavi Nannaya University were randomly assigned to either an experimental group (n=20), which underwent Pilates training, or a control group (n=20), which followed their regular routine without additional training. Pre- and post-intervention assessments were conducted using the McGill Core Endurance Test, Standing Long Jump Test, and Y-Balance Test. The results revealed significant improvements in core endurance, explosive power, and dynamic balance in the experimental group, while no substantial changes were observed in the control group. These findings suggest that Pilates-based training enhances neuromuscular coordination, core stability, and functional strength, which are critical for performance in high-intensity sports like Kabaddi. Given its effectiveness, integrating Pilates into the training regimens of contact sport athletes is recommended for improving performance and injury prevention. Future research should explore the long-term effects of Pilates and its comparative benefits with other strength training modalities.